SiGOG: simulated GPS observation generator - Mohino, Elsa (2005)
For many applications, access to unbiased or error-controlled global positioning system (GPS) observations can be very useful. This paper is devoted to the description of simulated GPS observations generator (SiGOG), a software that simulates GPS observations. It presents the results of tests of SiGOG accuracy using GPS processing software, and demonstrates its successful performance as a differential GPS (DGPS) correction provider.